2016
DOI: 10.1212/nxi.0000000000000207
|View full text |Cite
|
Sign up to set email alerts
|

Immunoadsorption therapy in autoimmune encephalitides

Abstract: Objective:It was hypothesized that in encephalitides with autoantibodies directed to CNS surface antigens an antibody-removing intervention might speed up recovery.Methods:The outcome of autoimmune encephalitis in 19 patients with antibodies against surface antigens (leucine-rich, glioma inactivated 1 [LGI1], n = 3; contactin-associated protein-2 [CASPR2], n = 4; NMDA receptor [NMDAR], n = 7) and intracellular antigens (glutamic acid decarboxylase [GAD], n = 5) after immunoadsorption in addition to corticoster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 38 publications
2
63
1
3
Order By: Relevance
“…Given the direct pathogenetic role of NMDAR-Abs, the use of apheresis therapy is very reasonable. The efficacy of immunoadsorption seems to be similar to those of plasma exchange [47,48]. As expected, an early immunotherapy ( < 40 days after initial manifestation) is associated with a significantly better prognosis [43].…”
supporting
confidence: 67%
“…Given the direct pathogenetic role of NMDAR-Abs, the use of apheresis therapy is very reasonable. The efficacy of immunoadsorption seems to be similar to those of plasma exchange [47,48]. As expected, an early immunotherapy ( < 40 days after initial manifestation) is associated with a significantly better prognosis [43].…”
supporting
confidence: 67%
“…Clinical trials using tryptophan IA showed rapid response of neurologic symptoms being refractory to drugbased strategies, for example, in patients with myasthenic crisis [22,23] . In autoimmune encephalitides, IA led to improvement in up to 86% of patients with antibodies directed to CNS surface antigens [24,25] . Reduction of serum antibodies with IA also resulted in the reduction of antibodies in CSF.…”
Section: Discussionmentioning
confidence: 99%
“…Three major mechanisms of action for IA in autoantibody-mediated neurological diseases act together: immediate intravascular reduction of antibody and immune complex concentration, pulsed induction of antibody redistribution, and subsequent immunomodulatory changes [25,27] . The mechanism of the effectiveness of IA for MS is not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…These observations, coupled with the highly heterogeneous phenotypes of patients with NMDAR antibodies in serum but not CSF, may suggest that the predicted natural diffusion of NMDAR‐IgG into the CNS is insufficient to generate this encephalitis phenotype. Yet, maybe the soluble autoantibodies do play a role in ongoing disease as plasma immunoabsorption of IgG leads to a fall in CSF autoantibodies and correlates with improvements in clinical status . The relative contributions of serum autoantibody transfer into the CNS and the degree of immune cell infiltration may vary across diseases but also within diseases, and could determine the likelihood of amelioration with plasma exchange or predict the need for future intrathecal‐directed therapies.…”
Section: The Therapeutically Relevant Immunologymentioning
confidence: 99%